Construction of polyoxometalates from dynamic lacunary polyoxotungstate building blocks and lanthanide linkers1. Issue 25 (7th July 2015) - Li, Lu-Lu; Han, Hua-Yan; Wang, Yong-Hui; Tan, Hua-Qiao; Zang, Hong-Ying; Li, Yang-Guang
<x xml:space="preserve">Abstract</x> New polyoxometalates have been constructed from the dynamic building block B-α-SbIIIW9O33 and lanthanide (Ln) linkers via a stepwise synthetic strategy, exhibiting luminescent properties with their Tb- and Dy-derivatives.